Pituitary Hormones mRNA Abundance in the Mediterranean Sea Bass Dicentrarchus labrax: Seasonal Rhythms, Effects of Melatonin and Water Salinity - Falcón, Jack; Herrero, Maria Jesus; Nisembaum, Laura Gabriela; Isorna, Esther; Peyric, Elodie; Beauchaud, Marilyn; Attia, Joël; Covès, Denis; Fuentès, Michael; Delgado, Maria Jesus; Besseau, Laurence (Frontiers in Physiology, 2021)
In fish, most hormonal productions of the pituitary gland display daily and/or seasonal rhythmic patterns under control by upstream regulators, including internal biological clocks. The pineal hormone melatonin, one main output of the clocks, acts at different levels of the neuroendocrine axis. Melatonin rhythmic production is synchronized mainly by photoperiod and temperature. Here we aimed at better understanding the role melatonin plays in regulating the pituitary hormonal productions in a species of scientific and economical interest, the euryhaline European sea bass Dicentrarchus labrax. We investigated the seasonal variations in mRNA abundance of pituitary hormones in two groups of fish raised one in sea water (SW fish), and one in brackish water (BW fish). The mRNA abundance of three melatonin receptors was also studied in the SW fish. Finally, we investigated the in vitro effects of melatonin or analogues on the mRNA abundance of pituitary hormones at two times of the year and after adaptation to different salinities. We found that (1) the reproductive hormones displayed similar mRNA seasonal profiles regardless of the fish origin, while (2) the other hormones exhibited different patterns in the SW vs. the BW fish. (3) The melatonin receptors mRNA abundance displayed seasonal variations in the SW fish. (4) Melatonin affected mRNA abundance of most of the pituitary hormones in vitro; (5) the responses to melatonin depended on its concentration, the month investigated and the salinity at which the fish were previously adapted. Our results suggest that the productions of the pituitary are a response to multiple factors from internal and external origin including melatonin. The variety of the responses described might reflect a high plasticity of the pituitary in a fish that faces multiple external conditions along its life characterized by marked daily and seasonal changes in photoperiod, temperature and salinity